2021
DOI: 10.1002/est2.302
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of electric vehicles: A case study

Abstract: Personal transportation is prevalent in Brunei Darussalam because of the lack of adequate public transportation. However, Brunei is not immune to the effects of climate change and as such, has launched a national policy to mitigate the impacts. As electric vehicles presently are very rare to Brunei, this article seeks to determine the total cost of ownership of internationally popular electric vehicles (EVs) and internal combustion engine vehicles (ICEVs) to put things in perspective for the Brunei market. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These studies, however, simplify their analysis by ignoring the discounted effect of money. Our previous works [7,8,19] related to electric vehicles have considered present value calculations and concluded that neither EVs, EV vehicles, nor EV charging infrastructure are yet able to compete with ICEVs without additional incentives by the government. Conversely, Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies, however, simplify their analysis by ignoring the discounted effect of money. Our previous works [7,8,19] related to electric vehicles have considered present value calculations and concluded that neither EVs, EV vehicles, nor EV charging infrastructure are yet able to compete with ICEVs without additional incentives by the government. Conversely, Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [19] has argued that it is necessary to perform analysis using local parameters to determine economic feasibility due to the complex interactions between the cost components of EVs and ICEVs. Other important parameters that factor into EV attractiveness include the driving range, availability of infrastructure, and charging time of EVs in comparison to ICEVs.…”
Section: Model For Ev Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Against the background of the traditional fossil energy shortage crisis and sustainable green development path (Ranjan Kumar and Kumar, 2020;Kalair et al, 2021;Li et al, 2022), it is encouraging that new energy electric vehicles (NEEVs) have been rapidly popularized worldwide due to their inherent advantages of zero harmful gas emissions, low energy consumption and non-pollution, high efficiency, and the use of more environmentally friendly electric energy as power sources (Buenger and Michalski, 2018;Mihet-Popa and Saponara, 2018;Hossain et al, 2022a;Cheok et al, 2022). Compared with the conventional internal combustion engine (ICE), NEEVs have more electronic and electrical equipment, including a power battery pack, inverters, traction electromotors, controllers, and a busbar cable, as shown in Figure 1 (Kene et al, 2021;Hossain et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%